2014
DOI: 10.3109/03008207.2014.923855
|View full text |Cite
|
Sign up to set email alerts
|

Plithotaxis, a collective cell migration, regulates the sliding of proliferating pulp cells located in the apical niche

Abstract: Using the proliferating cell nuclear antigen (PCNA) immunostaining, we previously identified, after pulp exposure, three zones of proliferating cells in the rat molar pulp. Zones I and II were in the crown near the pulp. Zone III was near the apex revealing a recruitment of mitotic cells at distance from the lesion. To gain further insight into the spatio-temporal evolution of proliferating pulp cells of zone III, we performed a longitudinal study of PCNA staining in rat molar mesial root at 3, 8, and 15 d aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
(10 reference statements)
0
9
0
2
Order By: Relevance
“…To accomplish this, a source of progenitor cells (erroneously referred to as 'SCs') is required. These cells must first be directed from their niche to the damaged area through chemotaxis or plithotaxis (Hirata et al 2014). Once the cells have migrated to contact the biomaterial, they must differentiate into mineral-secreting cells, at which point dentine synthesis is triggered.…”
Section: Is Pulp Exposure a Negative Factor?mentioning
confidence: 99%
“…To accomplish this, a source of progenitor cells (erroneously referred to as 'SCs') is required. These cells must first be directed from their niche to the damaged area through chemotaxis or plithotaxis (Hirata et al 2014). Once the cells have migrated to contact the biomaterial, they must differentiate into mineral-secreting cells, at which point dentine synthesis is triggered.…”
Section: Is Pulp Exposure a Negative Factor?mentioning
confidence: 99%
“…These cells migrate from the central part of the pulp to the lateral subodontoblastic boundaries. Then, they slide from the root towards the coronal part of the pulp where they underwent terminal differentiation (Hirata et al 2014), suggesting that apical progenitor cells are mobilized and contribute to pulp regeneration. In vitro, all these heterogeneous cell populations (DPSCs, SHEDs, SCAPs) have the ability to differentiate into odontoblasts, osteoblasts, and adipocytes as well as even into neuron-like cells.…”
Section: Cell Sources For Tooth Regenerationmentioning
confidence: 99%
“…They multiply and slide in the root pulp beneath the odontoblast/sub-odontoblast layers. PCNA labeled cells are located mainly in the apical part [20]. Six et al, [21] have shown that after 2 weeks, labeled cells become undetectable in the root.…”
Section: Dental Pulp Regeneration and Mineralizationmentioning
confidence: 99%